2011
DOI: 10.1074/jbc.m110.139261
|View full text |Cite
|
Sign up to set email alerts
|

A Zinc Finger Protein, TbZC3H20, Stabilizes Two Developmentally Regulated mRNAs in Trypanosomes

Abstract: CCCH zinc finger proteins (ZC3Hs) are a novel class of RNA-binding protein involved in post-transcriptional mechanisms controlling gene expression. We show TbZC3H20 from Trypanosoma brucei, the causative agent of sleeping sickness and other diseases, stabilizes two developmentally regulated transcripts encoding a mitochondrial carrier protein (MCP12) and trans-sialidase (TS-like E). TbZC3H20 is shown to be an RNA-binding protein that is enriched in insect procyclic form T. brucei and is the first ZC3H discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 54 publications
7
45
0
Order By: Relevance
“…ZFP1 was one of the first trypanosome RBPs to be implicated in development [56], was shown to be transiently upregulated during the differentiation from bloodstream to procyclic forms and consistent with our data was expressed at higher levels in established procyclic cells. ALBA2 was previously identified to interact with regulatory elements in the 3’ UTR of GPEET procyclin mRNA [57] and ZC3H20 is required for growth of procyclic forms [58], which fits our transcriptome data. Another noteworthy RBP is PUF9 (Tb927.1.2600), which was most prominent in the proventriculus transcriptome.…”
Section: Resultssupporting
confidence: 82%
“…ZFP1 was one of the first trypanosome RBPs to be implicated in development [56], was shown to be transiently upregulated during the differentiation from bloodstream to procyclic forms and consistent with our data was expressed at higher levels in established procyclic cells. ALBA2 was previously identified to interact with regulatory elements in the 3’ UTR of GPEET procyclin mRNA [57] and ZC3H20 is required for growth of procyclic forms [58], which fits our transcriptome data. Another noteworthy RBP is PUF9 (Tb927.1.2600), which was most prominent in the proventriculus transcriptome.…”
Section: Resultssupporting
confidence: 82%
“…ZC3H21 also was found to bind the EP2 mRNA; binding by ZC3H20 was just below our cut‐off. The two mRNAs that Ling et al () had previously shown to be bound to ZC3H20, encoding a trans ‐sialidase (Tb927.5.440) and the mitochondrial carrier MCP12 (Tb927.10.12840), were bound to both ZC3H21 and ZC3H20 in our analysis. We independently confirmed binding of ZC3H20 to the mRNAs encoding Aquaporin 1 and GPEET procyclin by pull‐down followed by semi‐quantitative PCR: Figure b shows that these two mRNAs were enriched relative to the tubulin control.…”
Section: Resultssupporting
confidence: 55%
“…Ling et al (Ling, Trotter, & Hendriks, ) showed that RNAi that simultaneously targeted ZC3H20 and ZC3H21 inhibited procyclic form trypanosome growth. Microarray experiments revealed that RNAi resulted in reduced levels of six RNAs, and increases in another ten.…”
Section: Introductionmentioning
confidence: 99%
“…T. brucei has forty-nine CCCH zinc finger proteins, some of which have been implicated in control of gene expression [33], [34], [35], [36], [37], [38], [39]. So far, however, none has been shown to have a destabilising function.…”
Section: Introductionmentioning
confidence: 99%